Criminal Policy on Adultery in Indonesia within Law Number 1 of 2023 Concerning the Criminal Code - Maesyaroh, Dewi; Sulistyanta (International Journal of Sustainability in Research, 2024)
The criminal policy for handling adultery offenses in Indonesia has undergone significant changes with the enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP). Article 411(1) in the new KUHP expands the definition of adultery, covering not only sexual relations between a man and a woman where one or both are married but also including sexual relations outside of marriage, whether the partners are married or not. This study aims to evaluate this criminal policy by examining the legal, social, and human rights implications of the expanded definition of adultery. The methodology used in this research is normative juridical analysis with a legislative and conceptual approach. The results of the study indicate that although this policy is intended to uphold the moral and ethical values of society, the expanded definition of adultery may raise controversies related to individual privacy and the potential criminalization of consensual adult behavior. This research recommends further evaluation of the implementation of this policy, considering the balance between protecting the moral values of society and respecting human rights.